x2 + 4x - 12 = 0 so (x+6)*(x-2) = 0 so x = -6 or x = 2
----
To solve the quadratic equation x2 + 4x - 12 = 0, you can use two different methods:
1: Reduce it to its factors:
x2 + 4x - 12 = 0 is the same as (x + 6)(x - 2) = 0. But this can only be correct if one of the factors is zero which only happens when x = -6 or x = 2. That is the solution.
2: Use the quadratic solution formula:
x2 + 4x - 12 = 0 is of the form ax2 + bx + c = 0 with a = 1, b = 4, and c = -12.
Substitute these values into the formula x = (-b ± sqrt(b2 - 4ac)) / 2a and you get x = (-4 ± sqrt(16 - (-48)) / 2 = (-4 ±sqrt(64)) / 2 = (-4 + 8) / 2 or (-4 - 8) / 2 = 4 / 2 or -12 / 2 so x = 2 or x = -6